Dual-Signal Cascaded Nucleic Acid Amplification Circuit-Loaded Metal-Organic Frameworks for Accurate and Robust Imaging of Intracellular MicroRNA - Liu, Sijia (Langmuir : the ACS journal of surfaces and colloids, 2023)
Cascaded signal amplification technologies play an important role in the sensitive detection of lowly expressed biomarkers of interests yet are constrained by severe background interference and low cellular accessibility. Herein, we constructed a metal-organic framework-encapsulating dual-signal cascaded nucleic acid sensor for precise intracellular miRNA imaging. ZIF-8 nanoparticles load and deliver FAM-labeled upstream catalytic hairpin assembly (CHA) and Cy5-modified downstream hybridization chain reaction (HCR) hairpin reactants to tumor cells, enabling visualization of the target-initiated signal amplification process for double-insurance detection of analytes. The pH-responsive ZIF-8 nanoparticles effectively protect DNA hairpins from degradation and allow the release of them in the acid tumor microenvironment. Then, intracellular target miRNAs orderly trigger cascaded nucleic acid signal amplification reaction, of which the exact progress is investigated through the analysis of the fluorescence recovering process of FAM and Cy5. In addition, DNAZIF-8 nanoparticles improve measurement accuracy by dual-signal colocalization imaging, effectively avoiding nonspecific false-positive signals and enabling in situ imaging of miRNAs in living cells. A dual-signal colocalization strategy allows accurate target detection in living cells, and DNA@ZIF-8 provides a promising intracellular sensing platform for signal amplification and visual monitoring